ANALISA KINERJA KEUANGAN DAERAH KABUPATEN PASER - Agus Munandar; Saputra Saputra (LPPM Institut Pendidikan Nusantara Global, 2023)
The recent outbreak of the Covid-19 virus presents new challenges for government agencies to manage their financial performance and financial reporting responsibly. Financial analysis is needed to analyze how the position and financial performance, and evaluate the operational performance of an agency in the future. The impact of this pandemic was also felt by Paser district with a decrease in regional economic growth. The purpose of this study is to understand how operational and financial performance in the Paser district local government in the period 2020 to 2021. This study uses a descriptive-quantitative approach by examining the calculation of the level of financial independence, efficiency and effectiveness, and also regional operations including the allocation of operating and capital expenditure costs. The results of the study show that Paser district is generally in a good financial position, but there are still some financial aspects that need to be improved in the coming financial year. Paser Regency needs to be more specific in setting revenue targets during the Covid-19 pandemic by observing trends in regional economic development and the possibility of enacting and implementing policies that maximize Local Original revenues so that they do not always depend on the contribution of the central government. Then, Paser Regency will be able to reduce operational costs and increase investment costs for